POLICY DEVELOPMENT IN METHODIST CHURCH NIGERIA, 1962-2020 (2023)
Policy development, an iterative process designed to help organisations advance policies to make them run efficiently in the realisation of their corporate objectives, is pivotal for organisational success, including the Methodist Church Nigeria (MCN). Existing studies on MCN have focused largely on historical development, renewal movements and doctrinal exegesis, with scant attention paid to its policy development. This study was, therefore, designed to examine policy development in MCN, which was orchestrated by the constitutional reforms from 1962, when the Church was granted autonomy from the British Methodist, to 2020, when the MCN held Constitutional Conference and reviewed the MCN Constitution, 2006. This was with a view to identifying the trends in policy development, its attendant benefits and challenges to the church. Anthony Giddens’ Structuration Theory was adopted as the framework, while the descriptive design was used. The purposive sampling technique was used to select 31 members of the clergy and 33 members of the laity based on their experience on policy issues in MCN. In-depth interviews were conducted with 14 episcopates, seven presbyters, eight priests, two deacons, one deaconess, four evangelists, four lay presidents, 10 stewards, seven fellowship presidents and seven former lay officers because they were involved as policymakers and implementers in the Conference area. Church records and the MCN Constitutions, 1962, 1976, 1990 and 2006, were consulted. The data were thematically analysed. The policy developments in MCN was a reflection of the changing dynamics in administering the church. The Deed of Foundation, 1962, granted the Church autonomy, while the MCN Constitution, 1976, addressed ecumenical matters with the introduction of Episcopacy and the adoption of titles, such as Patriarch, Archbishops and Bishops. The MCN Constitution, 1990, focused on reconciliation and reunification of the church after 14 years of internal crises. The MCN Constitution, 2006, which was in use until 2020 repositioned the church for effective ministry. The benefits derived from the policies include the introduction of new methods, such as the reordering of the ministry, charismatic worship and numerical growth from two districts at autonomy to 80 dioceses in 2020. The policies equally enhanced the national impact of the church in the education and health sectors, while it achieved global relevance in international outreach mission to Gabon, Togo, Dubai, United Kingdom and United States of America. Moreover, MCN’s leadership role in World Methodist Council was firmly established. However, there was the erosion of Methodist heritage and traditions, like simple hierarchies of priesthood and unelaborate liturgy as a result of the policy. There were also the Presidential and Patriarchal conflict from 1976 to 1990; partial implementation of the policies and financial burdens were evident in the irregular payment of Church workers’ salaries. Social change underpinned policies for autonomy, episcopacy and repositioning in Methodist Church Nigeria, from 1962 to 2020, with attendant benefits and challenges.